Human Resource Empowerment Regarding the Operation of TPS 3R Assets - Rahmat, Rahmat; Zamroni, M Afif (Sahwahita: Community Engagement Journal, 2024)
This article provides an overview of the empowerment of Human Resources that have TPS 3R Assets. Berat Kulon, Kemlagi District is one of the villages that has the potential for the best TPS 3R asset management in Mojokerto Regency, which was originally able to rise with the large amount of waste in the operation of Village Assets, namely TPS 3R. Precisely since the Corona pandemic in early 2020, there has been a spike in the amount of waste in this village which then resulted in piles of garbage everywhere, however, there are also small groups of residents who take advantage of this momentum to increase the economic income of residents around Berat Kulo Village, one of which is by managing waste into handicrafts in the form of bags, but this business did not have time to develop, after the pandemic, residents returned to sugar cane farming which has indeed been very much pursued by residents. The purpose of this service is to emphasize building awareness of empowering Human Resources (HR) through the operation of TPS 3R Assets. Utilizing the Asset Based Community Development (ABCD) approach, the results of the community service are 1) Implementation of human resource empowerment for the operation of TPS 3R Assets and 2) Assistance in the operation of TPS 3R Assets through, a) Waste Management Education Seminar through TPS 3R, b) Implementation of the August 17th competition in the context of environmental cleanliness creativity, c) Procurement of garbage signs, and d) Procurement of garbage bins.